From darkness to hope: A journey through patient experience - Janell Ross (The Beryl Institute, 2017)
After beating Hodgkin's Lymphoma, we believed our interaction with the healthcare community would be through routine check-ups. Little did we realize radiation scaring would lead to a complex diagnosis with no viable treatment options locally. The journey took us to the Cleveland Clinic where we tapped into something bigger than the latest in medical breakthroughs; we lived the patient experience. This is a true, personal story of tragedy, comfort and resilience followed by a realization of a heart's desire to make a difference for others in the patient experience field.